The Effectiveness concentration of some fungicide with mix by peat water on palm oil leaf spot disease (Curvularia sp.) in vitro - Deni Yolanda Sinaga; Lahmuddin Lubis; Fatimah Zahara; Agus Eko Prasetyo (Jurnal Agroekoteknologi, 2017)
This research was to study response of  the effectiveness fungicides with different concentrations on the leaf spot disease(Curvularia sp.)in vitro. This research was conducted at Center of Oil Palm Research, Marihat, Pematang Siantar. The method used factorial completely randomized design with three factors and three replications. The first factor was kind of fungisida active ingredients (mancozeb, metalaxcyl, benomyl, buirimat, and tebuconazole), the second factor was water solvent (normal water, shallow peat water (50 cm – 100 cm), medium peat water (101 cm – 200 cm) and depth peat water (201 cm -300 cm)) and third factor was concentrationsof  fungicide(1 ml/l (g/l), 2ml/l (g/l) and 3ml/l (g/l) . The results showed Tebukonazol fungicide active ingredient was able to inhibit the groth of leaf spot leaf disease (Curvularia sp.) and the most effective concentration is 2 ml/l using the medium peat water solvent